To Evaluate the Effectiveness of Lactic Acid Produced by Fermentation of Selected Vegetable Wastes in the Treatment of Faecal Sludge - Mwebia, Tyson Mwimathiri; Mugo, Dr. Cynthia (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
The utilization of faecal sludge in agriculture and nature holds significant promise, but its practical application is constrained due to the presence of harmful microorganisms. Implementing effective sludge treatment methods can help reduce these pathogens to levels that meet the acceptable standards set by the World Health Organization (WHO). In developing countries, there is a lack of sufficient information about suitable treatment options for faecal sludge derived from On-Site Sanitation (OSS) facilities. This research aimed at evaluating the effectiveness of lactic acid derived from fermented tomato, cabbage, and carrot wastes as a cost-effective pre-treatment method for faecal sludge collected from OSS facilities. To achieve this, equal amounts of fresh tomato, cabbage, and carrot wastes were collected and subjected to pre-treatment and lacto-fermented for six days at 370C. pH and lactic acid yield were monitored daily. TLC was used as a qualitative test to determine the presence of lactic acid. Lactic acid was quantified using UV-Vis spectrophotometry. A decrease in the pH levels in all the reactors indicated that fermentation had occurred. The lactic acid yields were 1.24, 1.07, 0.93 mg/ml for carrot, cabbage and tomato wastes respectively, indicating that carrot waste had the highest mean lactic acid yield while tomato had the lowest yield. Lactic acid presence in fermented tomato and cabbage waste was confirmed by the presence of yellow spots with a retention factor Rf 0.54 that was observed in tomato and cabbage waste. These results indicated that fermented vegetable waste can be a suitable substrate in the production of lactic acid.